Comparison of a modified flow cytometry osmotic fragility test with the classical method for the diagnosis of hereditary spherocytosis. Issue 5 (16th September 2021) - Shahal‐Zimra, Yael; Nosgorodcky, Yuval; Eshel, Elizabeth; Rotem, Zohar; Ross, Liron; Pickholtz, Itay; Rabizadeh, Esther; Chezar, Judith
Abstract: Background: Hereditary spherocytosis (HS) is the most common inherited hemolytic anemia. The flow cytometric test using eosin‐5′maleimide (EMA) is a well‐established diagnostic method. However, in order to improve HS detection, it is recommended that EMA and an osmotic fragility test (OFT) both be performed. OFT is time consuming and labor intensive. We used a flow cytometric (FOFT) adaptation of the classical OFT reported by Yamamoto. We compare the FOFT to the classical OFT including practical data and propose options for simplifying this method. Methods: Suspected and known HS patients and controls were tested by the following methods: EMA, OFT, and FOFT including some modifications. Results: The FOFT method is robust and correlates to loss of red blood cells. OFT and FOFT gave similar results in healthy controls and four HS patients. Normal range for FOFT in 70 adults is shown and can be used as a reference value. Neonates should have their own normal range defined. Overnight sample incubation at 37°C did not add information to the FOFT results. Conclusion: Our modified Yamomoto FOFT can replace the classic OFT as the addition to EMA for the diagnosis of HS. The use of flow cytometry in both these methods requires small sample volume, is reproducible, simpler, and produces results more rapidly.